Criminal Responsibility of the Perpetrator of Obstruction of Justice in Corruption Crimes - Aryani, Esti; Jumiati, Agatha; Pamungkas, Nova Satria (Indonesian Journal Publisher, 2025)
This research aims to examine the criminal liability of obstruction of justice perpetrators in corruption offenses and analyze the existence of regulations on obstruction of justice in current and future legislation.This research is a normative legal study that uses a case study approach, involving the examination of specific cases from various legal aspects. The case approach is conducted by examining cases related to the issues faced that have become court decisions with permanent legal force. In the case currently under examination, the defendant Friedrich Yunadi, who is a lawyer, was proven legally and convincingly guilty of the crime of